New Stratified Bayesian Estimators Using Warner’s Randomized Response Technique Through Mixed Priors - Adepetun, A. O.; Adewara, A. A. (Journal of Scientific Research, 2018)
In this paper, we propose new stratified Bayesian estimators of population proportion of a sensitive trait by adopting a mixture of alternative beta distributions as quantification of prior information in a stratified random sampling situation. Data were collected through Warner’s randomized response technique. To study the performance of the newly developed stratified estimators, mean squared error and absolute bias were used as performance criteria. The proposed estimators were compared with the existing one. We observed that the proposed estimators are more sensitive to responses than the existing one at various sample sizes respectively.